(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Patients with mass in the right iliac fossa may consent the surgeon, paediatrician or gynaecologist. Thus, proper Knowledge of anatomy and pathological process that occur within the abdomen are essential for a Clinical diagnosis and management. The objective of this study was to interpret etiopathology, clinical presentation, differential diagnosis and management of mass in the right iliac fossa. Methodology: 50 cases with mass in the right iliac fossa (RIF) were included in the study. Investigations such as Ultrasonography, colonoscopy and CT scan were done. Results: During this study period, a total number of 10 cases of appendicular abscess and 22 cases of appendicular mass were taken. 11 cases of ileocecal Koch’s were encountered. Patients had constitutional symptoms like pain, fever, weight loss etc. Specimens was observed after Right hemicolectomy, interval appendicectomy, ileoascending resection anastomosis microscopically and histopathological diagnosis. 2 cases of carcinoma ascending colon and 2 cases of carcinoma caecum were seen. Filling defect and mucosal irregularities was seen in Contrast enema. Conclusions: This study conclude that appendicular mass is the commonest pathology in right iliac fossa amongst all and conservative treatment followed by interval appendicectomy is the best way of treatment. Ileocecal tuberculosis is second and Carcinoma of the colon is third common causes for mass in the right iliac fossa. These cases having a good prognosis, if properly treated and diagnosed. The other rare causes of mass in the right iliac fossa are intussusception, psoas abscess.